The analysis of Business Competition Law Against the Abuse of Trademark Holders Exclusive Rights - Syarifaini, Indah Utami; Deviany, Oky; Sitorus, Winner (Budapest International Research and Critics University, 2022)
This study aims to find and describe the criteria for abuse of the exclusive rights of brand holders. This research was conducted in Makassar using normative research methods by referring to the applicable legal rules and principles. In addition, it uses a comparative approach to find out the laws in force in other countries related to IPR and Business Competition Law. It provides an overview by presenting case illustrations to harmonize with applicable regulations in Indonesia. The collected material is then described to obtain a clear picture and answer the problems studied. The results obtained indicate that brand holders can abuse the exclusive rights of brand holders by looking at the criteria based on the IPR rules and the Business Competition Law and the illustrations of the cases described in this paper.